2020
DOI: 10.29271/jcpsp.2020.02.172
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the Size and Location of the Mass and Hilar and Mediastinal Lymph Node Metastasis in Early and Locally Advanced Non-small Cell Lung Cancer

Abstract: The tumor, lymph node and metastasis (TNM) staging system, developed by Denoix in 1946, was adapted to lung cancer in 1968 by the Union for International Cancer Control (UICC) and in 1973 by the American Joint Committee on Cancer (AJCC). Since 1986, for lung cancer, TNM staging system has been used under the title of International Lung Cancer Staging System. Today, the 8th edition of lung cancer TNM staging system, released in 2017, is being used. 2,4,5 Mediastinal lymph node staging is one of the most crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Upper lobe NSCLCs are more likely to metastasize to the mediastinal LN, which is the underlying theory for dedicated lung lymphadenectomy [10,23,24]. Our results also suggested that the pT stage was a risk factor for station 4R metastasis, which was in agreement with other studies showing a relationship between tumor size and mediastinal LN metastasis [25,26]. Zhang et al suggested that systematic LN dissection should be performed, since tumor size was an independent risk factor for LN metastasis in patients even with pT1 stage lung adenocarcinoma [27].…”
Section: Discussionsupporting
confidence: 91%
“…Upper lobe NSCLCs are more likely to metastasize to the mediastinal LN, which is the underlying theory for dedicated lung lymphadenectomy [10,23,24]. Our results also suggested that the pT stage was a risk factor for station 4R metastasis, which was in agreement with other studies showing a relationship between tumor size and mediastinal LN metastasis [25,26]. Zhang et al suggested that systematic LN dissection should be performed, since tumor size was an independent risk factor for LN metastasis in patients even with pT1 stage lung adenocarcinoma [27].…”
Section: Discussionsupporting
confidence: 91%
“…The number and area of MLNM are closely related to the surgical method, resection range and postoperative recurrence. 16 At present, CT, bronchoscopy, mediastinoscopy and thoracoscopy are the methods for clinical diagnosis of MLNM. However, invasive surgery is not easily accepted by patients before definite diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The lesion size is considered a critical predictor of the outcome in different types of cancers [ 18 , 19 , 20 ]. The increase in tumor size has been associated with mass-related complications like compression and hemorrhage, and with higher invasion and metastasis rates in cases of malignancies [ 20 , 21 ]. This will eventually result in more unfavorable management outcomes.…”
Section: Discussionmentioning
confidence: 99%